2012
DOI: 10.4236/pp.2012.34065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Use of Flavonoids on the Absorption and Tissue Distribution of Orally Administered Doses of Trace Elements in Rats

Abstract: The risk of pharmacokinetic polyphenols-trace elements interaction may undesirable therapeutic outcomes. We evaluate the long-term use of silibinin, epigallocatechin (ECGC), quercetin and rutin on the absorption and tissue distribution of zinc, copper and iron after single oral doses in rats. Five groups of rats received either with olive oil as control or one of the polyphenols silibinin, EPGC, quercetin or rutin, administered orally as oily solutions for 30 days. At day 30, a solution contains sulphate salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
4
4
0
Order By: Relevance
“…5 ment with the extract of C. sativum improved kidney damage. It has been shown that flavonoids could be interfering with iron absorption and act as an iron chelator compound (37,38). Previous studies confirmed that the iron-chelating properties of a plant directly related to its flavonoids content (39).…”
supporting
confidence: 48%
“…5 ment with the extract of C. sativum improved kidney damage. It has been shown that flavonoids could be interfering with iron absorption and act as an iron chelator compound (37,38). Previous studies confirmed that the iron-chelating properties of a plant directly related to its flavonoids content (39).…”
supporting
confidence: 48%
“…Therefore, it is important to determine the effective range of oral intake and pathophysiological condition in which these natural occurring avonoids are consumed. 21 In the present study, serum and splenic tissue levels of iron aer simultaneous administration of pharmacological doses of iron combined with equal doses of avonoids were evaluated. Our nding clearly showed that serum and tissues availability of iron increased signicantly compared with control group.…”
Section: Discussionmentioning
confidence: 99%
“…The positive metallic ion charge is shielded during chelation preventing the interaction of metal ion with negatively charged layer of mucin thereby increasing the lipophilicity and ease to get absorbed from intestinal enterocyte. 21 Complex of iron with quercetin may provide alternative pathway for iron absorption through glucose transporter. 30 The reported variation in levels of iron stores and ferroportin in the present study could be related to the differences between structural properties of different avonoids, including the position and number of hydroxyl groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the interactions between flavonoids and specific elements on laboratory animals and reported varying results depending on the polyphenols used and the elements examined. In detail, supranutritional doses of silibinin (100 mg/kg), epigallocatechin gallate (25 mg/kg), quercetin (50 mg/kg), and rutin (500 mg/kg) were added to rat nutrition and reported increased absorption of zinc, copper, and iron and their availability in brain, kidney, and liver [26]. Similarly, the extent to which different polyphenols (chlorogenic acid, caffeic acid, catechin, and rutin) influence zinc and copper absorption in rats was investigated by Coudray et al [27] and reported that polyphenols may decrease non-hem iron absorption and negatively affect zinc absorption in the rat.…”
Section: Introductionmentioning
confidence: 99%